The Protein Protocols Handbook - Walker, John M. (Humana Press, 1996)
In The Protein Protocols Handbook, I have attempted to provide a cross-section of analytical techniques commonly used for proteins and peptides, thus providing a benehtop manual and guide both for those who are new to the protein chemistry laboratory and for those more established workers who wish to use a technique for the first time. We each, of course, have our own favorite, commonly used gel system, g- staining method, blotting method, and so on; I'm sure you will find yours here. H- ever, I have also described a variety of altematives for many of these techniques; though they may not be superior to the methods you commonly use, they may nev- theless be more appropriate in a particular situation. Only by knowing the range of techniques that are available to you, and the strengths and limitations of these te- niques, will you be able to choose the method that best suits your purpose